The Erosion of Management's Rights Through Decisions in Plant Shutdown and Relocation Cases - Einbecker, Richard Charles (Academy of Management Journal, 1968)
The article presents a dissertation abstract titled ?The Erosion of Management's Rights Through Decisions in Plant Shutdown and Relocation Cases,? by Richard Charles Einbecker.